Prevalence of Anemia among Adolescent Girls in Rural Area of a District of Maharashtra - Nair, Abhilasha; Doibale, Mohan K (Indian Journal of Community Health, 2023)
Introduction: Nutritional anemia is one of India’s major public health problems. Adolescence is a vulnerable period in the human life cycle for the development of nutritional anemia. Anemia in adolescent girls contributes to maternal and foetal mortality and morbidity in future. Aim and Objectives: To estimate the prevalence of anemia among adolescent girls and to study the sociodemographic factors associated with anemia. Method: It was a community based cross sectional study in 10 villages of a district. 420 adolescent girls were interviewed using a predesigned, pretested questionnaire, and their anemic status was assessed by hemoglobin estimation. Results were analyzed by using percentage, proportion and Chi-square test, with the help of Microsoft Excel 2007 and SPSS version 20.0 statistical software. Result: Mean age of the study sample was 14.01 ± 2.57 years. The majority (64.8%) of the girls were Hindu by religion and belonged to a nuclear family (53.6%). 45.2 % were educated up to high school level. Most of the girls belonged to socioeconomic class IV (46.0%). The prevalence of anemia in this study was found to be 65.7%. The prevalence of mild and moderate anemia among study participants was 32.6 and 29.8%, respectively. A statistically significant association was found between the prevalence of anemia with age group, educational status of both father and mother, and status of attainment of menarche (p<0.05). Conclusion and Recommendation: The prevalence of anemia among adolescent girls was very high; therefore, attempts must be made to sensitize adolescents and their parents through health and nutrition education, information, education, and communication (IEC), and appropriate behavioral change communication (BCC) activities.